Salivary pH before and after cranberry juice consumption - Marunduri, Dwiana Lisany; Wihardja, Rosiliwati; Yohana, Winny (Faculty of Dentistry Universitas Padjadjaran, 2020)
Introduction: Cranberry (Vaccinium macrocarpon) is commonly consumed as a source of antioxidants. The cranberry juice has a sour and a little bit of bitter taste that can affect the salivary pH. The sour taste is a result of its high content of proanthocyanidin. Cranberry juice plays a role in maintaining oral and dental health. Cranberries’ flavonol and proanthocyanidin content play a role in preventing dental caries by preventing the growth of Streptococcus mutans. This study was aimed to compare the salivary pH before and after cranberry juice consumption. Methods: This research was quasi-experimental. The research population was the students from the Faculty of Dentistry Universitas Padjadjaran, and the sampling method was purposive sampling. Thirty-five male and female students with no history of systemic disease and drug administration, no orthodontics appliance and denture, were involved in this experiment. Students with lesions on oral mucosa were also excluded from this study. The pH measurement was performed with a digital pH meter to record the salivary pH ratio before and after consumption of cranberry juice. Before salivary pH comparison analysis was performed, the normality test was conducted, then the analysis was continued using the paired t-test. Statistical analysis was determined at α=0.05. Results: The average values of salivary pH ratio before and after consumption of cranberry juice were 6.714 and 7.246, respectively. The normality test showed that the p-value before and after consumption of cranberry juice were 0.143 and 0.285, respectively (p-value>0.05), which categorised in the normal distribution. The paired t-test statistical analysis showed the p-value of 0.001 (p-value<0.05), which considered as significant. This result indicated that there was a significant difference in the salivary pH before and after consumption of cranberry juice. Conclusion: The salivary pH is increasing after cranberry juice consumption.